In silico analyses of predicted substitutions in fibrinolytic protein 'Lumbrokinase-6' suggest enhanced activity. (November 2021) - Munawar, Sadam; Sagir, Muhammad; Mustafa, Ghulam; Ali, Muhammad Amjad; Niazi, Adnan Khan; Parvaiz, Aqsa; Yasmin, Farkhanda; Mansoor, Farukh; Kanwal, Shamsa; Rasheed, Majeeda; Kehfulvara, Hafiza; Ali, Habib; et al.
Graphical abstract: Highlights: Lumbrokinases are group of serine proteases. Serine found at position 214 in lumbrokinase improved the activity of lumbrokinase. In silico tools were used for characterization of mutant Lk-6 proteins. Serine-Valin214 substitution were direct activation of breaking Arg561-Val562 bond. The results of this study are step forward towards engineering smart lumbrokinases. Abstract: Lumbrokinases (LKs) belong to the group serine proteases capable to prevent thrombosis through the proteolysis of both plasminogen-bound and plasminogen-free fibrin molecules. The article presents improved activity of Lumbrokinase-6 (Lk-6) by suggesting the substitution of a Serine found at position 214 (Lk-6) with three other amino acids namely Glutamic acid, Proline and Valine. To characterize the stability, enzyme-substrate interaction and improved activity of three mutant Lk-6 proteins (Lk-Glu214, Lk-Pro214, Lk-Val214) In Silico tools were utilized. Subsequently, Lk-6 wild type and three mutant proteins were subjected to structure prediction, molecular modeling, phylogeny, molecular docking and Protein-Protein Interaction (PPI) using the In Silico tools. Collection and analysis of results revealed that substituted mutation at Ser214 with Valine214 can appreciably stabilize the overall structure of Lk-6 protein and makes its interaction with plasminogen activator physically powerful for higher plasmin activation. Similarly, Serine214 to Valine214 substitution resulted the direct activation of plasmin breakage at the Arg561-Val562 bond. The Arg-Val at position 561–562 in plasminogen and its connection at catalytic site have significantly shown that the predicted residue Valine214 could be further examined through genetic engineering of Lk-6 protein. Therefore, such results are potential steps towards the engineering of smart and active Lks.